Assessment of the distance of maxillary posterior tooth roots to the maxillary sinus using Cone Beam Computed Tomography Images - Subrata, Dwina Lathifah Ramadhani Wirahadi; Farizka, Intan; Arifin, Sariyani Pancasari Audry; Lubis, M. Novo Perwira; Palupi, Anggraeny Putri Sekar; Tanjung, Rizki (Ikatan Radiologi Kedokteran Gigi Indonesia, 2025)
Objectives: This research aims to determine the variation in the distance of maxillary posterior tooth roots to the maxillary sinus. Materials and Methods: This research employed a descriptive observational design using 68 samples of CBCT radiographs of individuals aged 20–40 years from Dental Radiology Installation of Dental & Oral Hospital, Faculty of Dentistry, Universitas Trisakti. The distance assessed in this study is the shortest vertical distance from the apices to the maxillary sinus floor of all roots in first premolars, second premolars, first molars and second molars. The measurements were performed using i-Dixel 2.2 software (Morita-Japan). Results: The result showed the mesiobuccal root of the second molar was the closest to the maxillary sinus, with a mean distance of -0.24 ± 1.23 mm. Conversely, the buccal root of the first premolar was the farthest, with a mean distance of 4.72 ± 3.11 mm. Conclusion: The proximity order of roots relative to the maxillary sinus, from closest to farthest, is as follows: mesiobuccal root of the second molar, distobuccal root of the second molar, palatal root of the first molar, distobuccal root of the first molar, mesiobuccal root of the first molar, palatal root of the second molar, palatal root of the second premolar, the single root of the second premolar, buccal root of the second premolar, palatal root of the first premolar, the single root of the first premolar, buccal root of the first premolar. Keywords: Cone Beam Computed Tomography, maxillary sinus, posterior teeth roots.